2001
DOI: 10.1007/s11627-001-0064-4
|View full text |Cite
|
Sign up to set email alerts
|

Callus formation and plant regeneration from immature and mature embryos of rye (Secale cereale L.)

Abstract: An efficient protocol was developed to regenerate entire plants from immature embryos of elite genotypes of rye as a prerequisite to plant transformation. Three winter genotypes and one spring genotype were tested using both immature and mature embryos as explants. Four types of callus initiation media and five kinds of regeneration media were tested in all possible combinations. Immature embryos gave much higher levels of plant regeneration than mature embryos, but mature embryos could be induced to regenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 38 publications
(52 reference statements)
2
24
0
Order By: Relevance
“…The use of growth regulators for in vitro regeneration has been extensively studied in grass and cereal tissue culture (Ward and Jordan 2001). The role of auxin (2,4-D) for induction of somatic embryogenesis is common in grasses and cereals, with optimum concentrations varying between different grass species studied (Wang et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The use of growth regulators for in vitro regeneration has been extensively studied in grass and cereal tissue culture (Ward and Jordan 2001). The role of auxin (2,4-D) for induction of somatic embryogenesis is common in grasses and cereals, with optimum concentrations varying between different grass species studied (Wang et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This is probably due to the fact that each shoot on embryogenic callus was not removed immediately as it formed. As Ward and Jordan (2001) reported, our study also sought to develop a method where plantlets could be regenerated directly on the callus. This minimizes the amount of time in culture, which can be important for minimizing somaclonal variation.…”
Section: Discussionmentioning
confidence: 99%
“…Plant regeneration has previously been achieved from callus cultures from mature embryos in cereals (Rueb et al 1994;Özgen et al 1998;Akula et al 1999;Ward and Jordan 2001). The use of mature embryos from dry seeds has several advantages: mature embryos are easy to handle, available year round and in bulk quantities.…”
Section: Introductionmentioning
confidence: 99%
“…species or cultivars (Bregitzer 1992). Moreover, callus quality varied considerably among genotypes (Vasil andVasil 1987, Islam 2010); and most barley varieties initiate friable and translucent callus (Hanzel et al 1985, Ward and Jordan 2001, Chauhan and Kothari 2004. Bregitzer et al (1998) also reported that the poor regeneration potential of modern cultivars is one current limitation of barley transformation.…”
Section: Introductionmentioning
confidence: 99%